2020
DOI: 10.3390/medicina56080381
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio and Systemic Immune-Inflammation Index—Biomarkers in Interstitial Lung Disease

Abstract: Background and objectives: The aims of the study were to evaluate the utility of neutrophil-to-lymphocyte ratio (NLR) and the systemic immune-inflammation index (SII) as inflammation markers and prognostic factors in patients with known interstitial lung disease secondary to connective tissue diseases (CTD-ILD) compared with idiopathic pulmonary fibrosis (IPF). Materials and Methods: Forty-two patients with known interstitial lung disease (21 with IPF and 21 with CTD-ILD) and 42 control matched healthy patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 35 publications
3
38
0
Order By: Relevance
“…Similar properties have also been exhibited by some blood cell dimensional indexes, such as the red blood cell distribution width (RDW), which has been reported to be an indicator of poor prognosis in IPF [ 10 , 35 ]. The values of combined blood cell count indexes in the present study were similar to those recently described in IPF patients [ 20 , 21 ]. In addition, by univariate correlation analysis, we found significant relationships between ratios of blood cell counts and lung functional parameters FEV1%, FVC% and DLCO%, indicating that the deterioration in lung function may be related to a higher inflammatory state in IPF patients.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar properties have also been exhibited by some blood cell dimensional indexes, such as the red blood cell distribution width (RDW), which has been reported to be an indicator of poor prognosis in IPF [ 10 , 35 ]. The values of combined blood cell count indexes in the present study were similar to those recently described in IPF patients [ 20 , 21 ]. In addition, by univariate correlation analysis, we found significant relationships between ratios of blood cell counts and lung functional parameters FEV1%, FVC% and DLCO%, indicating that the deterioration in lung function may be related to a higher inflammatory state in IPF patients.…”
Section: Discussionsupporting
confidence: 91%
“…Given the established relationship between IPF condition and some inflammation biomarkers [ 20 , 21 , 23 , 24 , 25 , 26 , 27 , 28 ], we sought to determine the prognostic capacity of the combined blood cell count indexes, a group of well-recognized biomarkers of inflammation obtained by the complete blood cell count test, that is routinely provided in clinical practice. Ratios of blood cell counts have shown to be effective in predicting the survival of those with acute and chronic diseases [ 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that neutrophils and platelets are involved in inflammation, which regulates the immune system [ 14 , 15 ], and lymphocytes in patients with CAP are consumed in the anti-infection immunity response [ 16 ]. Therefore, NLR and PLR are considered to be representative of the inflammatory status [ 17 , 18 ]. It has been reported that NLR and PLR may be alternative markers of CAP-related inflammation [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The systemic immune-inflammatory (SII) index is an integrated marker of systemic inflammation and it results from a combination of NLR and PLR. The SII index has been already extensively assessed as a marker of prognosis and mortality of patients with solid tumors or coronary artery disease [ 41 , 42 , 43 ]. Until now, very limited data is available concerning the relationship between SII index and psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%